Design proposal about a medical device that expedites the use of a biliary drainage after an invasive surgery performed on the digestive system - Álvarez-Agüero, María Fernanda (2019)
Conditions present within postoperative recovery of the patients that experienced a digestive system surgery are not the best due to lack of knowledge about the situation those involved go through, lack of information and support products; even more when the patient must use an invasive device to drain biliary fluids from the body. In order to provide a solution for this problem, it is developed a proposal  that applies two design methodologies,strategic design and thinking design, with the purpose of getting an integral product where both the user and the environment were important in the development which, in turn, comply with proposed objectives about prevention of relapses, psychological load decrease and trust increase during the products handling by users. Among the problems found, lost of independence of the patient to perform basic tasks and complexity on use of the biliary drain are highlighted. At the end of the study, it was possible to simplify the tasks related to the biliary drain about time as much as complexity, and it achieved to give major independence to the patient regarding the tasks that might increase the psychological load of those involved.